Catalyst and method for producing the same, and method for producing unsaturated hydrocarbon

By loading the catalyst of transition metal and fibrous carbon on the support, the problem of low selection rate in the dehydrogenation process of alkanes in the prior art is solved, and the effect of efficiently producing unsaturated hydrocarbons is achieved.

CN114728272BActive Publication Date: 2025-02-21MITSUBISHI CHEM CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202080079057.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-09-24
Filing Date
2020-11-11
Publication Date
2025-02-21
Estimated Expiration
2040-11-11

AI Technical Summary

Technical Problem

The prior art is difficult to achieve high selectivity in the process of alkane dehydrogenation, resulting in low production efficiency.

Method used

By supporting the transition metal and fibrous carbon on the support, a catalyst is formed and contacted with a mixed gas containing alkanes and carbon dioxide to achieve efficient manufacturing of unsaturated hydrocarbons.

Benefits of technology

This method significantly improves the selection and conversion rate of alkane dehydrogenation reaction and improves the production efficiency of unsaturated hydrocarbons.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114728272B_ABST
    Figure CN114728272B_ABST
Patent Text Reader

Abstract

The present invention provides a catalyst capable of producing unsaturated hydrocarbons with high selectivity in the dehydrogenation of alkanes, a method for producing the catalyst, and a method for producing unsaturated hydrocarbons. The catalyst is characterized in that a transition metal and carbon are supported on a carrier, and the carbon comprises fibrous carbon. The catalyst is brought into contact with a mixed gas containing alkanes and carbon dioxide to produce unsaturated hydrocarbons from the alkanes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a catalyst and a method for producing the same, and a method for producing an unsaturated hydrocarbon. Background Art

[0002] Generally, a method of producing olefins by dehydrogenating alkanes is known, and various catalysts used for the dehydrogenation have been studied.

[0003] For example, Patent Document 1 describes a dehydrogenation catalyst in which nickel and tin are supported on a composite carrier, wherein a specific amount of zinc oxide is supported on a specific γ-alumina carrier. In addition, an example of using the dehydrogenation catalyst to dehydrogenate isobutane to produce isobutene is described.

[0004] In addition, Patent Document 2 describes a catalyst in which zinc and a metal of Group VIIIA of the periodic table are supported on a specific zeolite carrier. In addition, a method for producing unsaturated hydrocarbons by dehydrogenating hydrocarbons in the presence of the catalyst is described. As an example, an example of producing butenes (1-butene, 2-butene, isobutene) by dehydrogenating n-butane using the catalyst is described.

[0005] In addition, Patent Document 3 describes a method for producing an oxidative dehydrogenation catalyst, comprising the following steps: a step (a) of dispersing silicate in water, a step (b) of adding a chromium element, a step (c) of adding a surfactant after step (a) or step (b), and a step (d) of performing a heat treatment at a temperature of 50 to 150° C. for 1 to 20 hours, and a step (d) of performing a heat treatment at a temperature of 200 to 700° C. for 1 to 10 hours. The method also describes a method for producing olefins from alkanes by contacting the obtained catalyst with a mixed gas containing alkanes and oxygen at a specific mixing ratio. As an example, an example of producing isobutylene from isobutane using the catalyst is described.

[0006] In addition, Patent Document 4 describes that in the hydrocarbon conversion step, a catalyst in which a transition metal is supported on a carrier is pretreated. However, since the pretreatment time is relatively short, 30 to 90 minutes, it is not possible to suppress the aggregation of the transition metal and achieve a high selectivity.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Laid-Open No. 9-75732

[0010] Patent Document 2: Japanese Patent Application Publication No. 2013-163647

[0011] Patent Document 3: Japanese Patent Application Publication No. 2014-140827

[0012] Patent Document 4: Japanese Patent Application No. 2018-520858 Summary of the invention

[0013] In the method of producing unsaturated hydrocarbons by dehydrogenation of alkanes, high productivity is expected, and therefore it is necessary to obtain them with a higher selectivity.

[0014] Therefore, an object of the present invention is to solve the problems caused by the above circumstances, that is, to provide a catalyst capable of producing unsaturated hydrocarbons with high selectivity in the dehydrogenation of alkanes, a method for producing the catalyst, and a method for producing unsaturated hydrocarbons.

[0015] According to one embodiment of the present invention, there is provided a catalyst characterized in that a transition metal and carbon are supported on a carrier, and the carbon includes fibrous carbon.

[0016] According to another aspect of the present invention, there is provided a method for producing a catalyst, comprising the following steps:

[0017] A step of mixing a solution containing a transition metal compound with a carrier, heating and removing the solvent to obtain a catalyst precursor,

[0018] a step of bringing the carbon-containing gas into contact with the catalyst precursor to form a catalyst loaded with transition metal and carbon,

[0019] In the step of forming the catalyst, the carbon-containing gas is brought into contact with the catalyst precursor, thereby forming and supporting fibrous carbon.

[0020] According to another aspect of the present invention, there is provided a method for producing unsaturated hydrocarbons, comprising bringing the above-mentioned catalyst into contact with a mixed gas containing an alkane and carbon dioxide to produce the unsaturated hydrocarbons from the alkane.

[0021] According to another aspect of the present invention, there is provided a method for producing unsaturated hydrocarbons, comprising producing a catalyst by the above-mentioned method for producing a catalyst, and then contacting a mixed gas containing an alkane and carbon dioxide with the obtained catalyst to produce unsaturated hydrocarbons from the above-mentioned alkane.

[0022] According to another aspect of the present invention, there is provided a method for producing an unsaturated hydrocarbon, comprising the following steps:

[0023] a step of bringing a carbon-containing gas into contact with a catalyst precursor in which a transition metal compound is supported on a carrier, thereby supporting carbon including fibrous carbon on the catalyst precursor to form a catalyst supported with a transition metal and carbon,

[0024] A mixed gas containing an alkane and carbon dioxide is brought into contact with the obtained catalyst to produce an unsaturated hydrocarbon from the alkane.

[0025] According to the present invention, a catalyst capable of producing unsaturated hydrocarbons with high selectivity in dehydrogenation of alkanes, a method for producing the catalyst, and a method for producing unsaturated hydrocarbons can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a SEM image of the catalyst of Example 2 of the present invention.

[0027] Figure 2 is Figure 1 The SEM image of shows a lattice-like dividing line. DETAILED DESCRIPTION

[0028] Hereinafter, a catalyst and a method for producing the catalyst, and a method for producing an unsaturated hydrocarbon (preferably an olefin) from an alkane according to an embodiment of the present invention will be described in detail.

[0029] (catalyst)

[0030] The catalyst according to the embodiment of the present invention is a catalyst in which carbon is supported on a carrier supported with a transition metal.

[0031] The catalyst is a solid catalyst having catalytic activity in the reaction of forming unsaturated hydrocarbons by dehydrogenation of alkanes. In the method for producing unsaturated hydrocarbons from alkanes described below, the catalyst is preferably used as a catalyst for the reaction of forming unsaturated hydrocarbons (preferably olefins) by dehydrogenation of alkanes.

[0032] In the catalyst, there is no particular limitation on the carrier for supporting the transition metal and carbon, and for example, at least one selected from silicon dioxide, aluminum oxide, zirconium oxide, and titanium dioxide can be used. One of these can be used alone, or two or more can be used in combination. Among these, aluminum oxide is preferred, and gamma-alumina is particularly preferred.

[0033] The particle size of the carrier can be appropriately selected, and it is preferred to adjust the particle size in a manner that the pressure loss in the catalyst layer of the reactor (e.g., reaction tube) filled with the obtained catalyst does not become too large. From the viewpoint of suppressing the pressure loss in the catalyst layer and ensuring the surface area of ​​the catalyst, the particle size of the carrier is preferably as small as possible, and when a sieve based on Japanese Industrial Standards (JIS) is used, it is preferably 3.5 mesh (mesh 5.6mm) or more, and particularly preferably 8.6 mesh (mesh 2.0mm) or more. On the other hand, from the viewpoint of the difficulty in handling the particulate component and the increase in the pressure loss when filled in the reactor on the reactivity, it is preferably 635 mesh (mesh 20μm) or less, and particularly preferably 280 mesh (mesh 53μm) or less.

[0034] The catalyst involved in the embodiment of the present invention can be filled into a reactor (such as a reaction tube) in a powder state. At this time, it is preferred to adjust the particle size in a manner that the pressure loss in the catalyst layer does not become too large. From the viewpoint of suppressing the pressure loss in the catalyst layer and ensuring the surface area of ​​the catalyst, the particle size of the catalyst is preferably as small as possible. In addition, from the viewpoint of suppressing the pressure loss in the catalyst layer, the catalyst can be mixed with other materials and can be filled after molding. As other materials, fillers (silica balls, alumina balls) that are inactive relative to the catalyst and do not deteriorate the catalyst performance can be used. In addition, molding can add a binder that does not deteriorate the catalyst performance to the obtained catalyst, and mix, heat and sinter. As a binder (sintering agent), silica, alumina, zirconium oxide, and diatomaceous earth can be cited. In addition, as the shape after molding, sheets, particles, spheres, and extrusions can be cited. By molding, strength and operability can be improved.

[0035] As the transition metal supported on the carrier, at least one selected from molybdenum, tungsten, chromium, nickel, iron, noble metals (Au, Ag, Pt, Pd, Rh, Ir, Ru, Os), vanadium, manganese, and zinc can be used, and multiple types can be used. Among these, nickel (Ni) is preferred from the viewpoint of cost and catalyst performance.

[0036] From the viewpoint of showing good activity as a catalyst, the amount of transition metal loaded on the carrier is preferably 1.0 mass% to 30.0 mass% relative to the carrier. By making the amount of transition metal loaded on the carrier more than 1.0 mass%, the transition metal particles present as active sites are easily maintained on the surface of the carrier, so the conversion rate of alkanes can be improved. In addition, by making the amount of transition metal loaded on the carrier less than 30.0 mass%, the aggregation of transition metal particles loaded on the carrier can be further suppressed, the surface area of ​​the active sites can be maintained larger, and the conversion rate of alkanes and the selectivity of olefins corresponding to the alkanes can be improved. Among the above, the amount of transition metal loaded on the carrier is more preferably more than 3.0 mass%, more preferably more than 5.0 mass%, particularly preferably more than 10.0 mass%, and most preferably more than 15.0 mass%. On the other hand, it is more preferably less than 28.0 mass%, more preferably less than 25.0 mass%, and particularly preferably less than 23.0 mass%. It should be noted that the amount of transition metal loaded on the carrier in the present invention can be measured using an X-ray fluorescence analyzer.

[0037] The catalyst of this embodiment further supports carbon containing fibrous carbon on the basis of transition metal as described above. The catalyst can improve the conversion rate of alkane and the selectivity of olefins corresponding to the alkane in the dehydrogenation reaction of alkane by supporting carbon containing fibrous carbon. The reason is not clear, but it is considered to be the following reason.

[0038] In common metal-supported catalysts, generally speaking, the metal particles on the carrier aggregate into coarse particles as the reaction proceeds, so that the surface area of ​​the active site decreases and causes a decrease in reactivity, and the structural change of the active site causes a decrease in selectivity. However, it is believed that by pre-loading carbon containing a specific amount of fibrous carbon on the basis of transition metals, the presence of carbon containing fibrous carbon can suppress the aggregation of transition metals caused by heat or vibration in the reaction, so that good active sites can be maintained, and the selectivity of alkanes and the selectivity of olefins corresponding to the alkanes and unsaturated hydrocarbons can be improved. It should be noted that in the present invention, when observed using a scanning electron microscope (SEM), carbon stretched into a fibrous shape (carbon present in a so-called elongated shape) is referred to as fibrous carbon. The cross-sectional shape of the carbon stretched into a fibrous shape (the shape of the cross section perpendicular to the long side direction) can be any one of a circle, an ellipse, a triangle, a quadrilateral, a polygon, etc., or it can be amorphous and can be a thin plate. In addition, the ratio of the length of the fibrous carbon to the average diameter of the cross section is not particularly limited. In addition, the fibrous carbon can be bent, can be linearly stretched, or can be branched.

[0039] The amount of carbon containing fibrous carbon loaded on the carrier is preferably 510% by mass or more, preferably 2500% by mass or less relative to the loaded transition metal. If the amount of carbon containing fibrous carbon loaded on the carrier is 550% by mass or more relative to the loaded transition metal, it is easy to obtain the effect of immobilizing the transition metal particles, so it is easy to suppress the agglomeration of transition metal particles in the reaction. As a result, the conversion rate of alkanes and the selectivity of olefins corresponding to the alkanes can be improved. As long as the carbon loaded on the carrier contains fibrous carbon, if the amount of carbon containing fibrous carbon is such a range, more sufficient above-mentioned effects can be obtained. The carbon loaded on the carrier contains fibrous carbon (there is fibrous carbon loaded on the carrier), which can be confirmed by scanning electron microscopy (SEM). The observation image obtained by SEM is divided into 12 equal grids, preferably forming fibrous carbon on the carrier to the extent that the presence of fibrous carbon can be confirmed in each grid.

[0040] On the other hand, if the amount of carbon including fibrous carbon loaded on the carrier is less than 2500 mass % relative to the loaded transition metal, it is possible to further prevent the transition metal particles from being excessively coated with carbon and thereby hindering the catalytic activity, thereby increasing the conversion rate of alkanes and the selectivity of olefins corresponding to the alkanes.

[0041] In the above, the amount of carbon including fibrous carbon loaded on the carrier is more preferably 700 mass % or more, particularly preferably 1000 mass % or more, and on the other hand, is more preferably 2300 mass % or less, particularly preferably 2000 mass % or less, relative to the loaded transition metal.

[0042] It should be noted that in the present invention, the amount of carbon including fibrous carbon supported on the carrier can be measured by using thermogravimetric and differential thermal analysis (TG-DTA) to raise the temperature to 1000° C. and start the measurement of the amount of carbon supported from the weight loss at that time. It should be noted that in the examples described later, the weight loss when heated to 200° C. is caused by the detachment of adsorbed water, so the weight loss in the process of heating from 200° C. to 1000° C. is calculated as the weight loss caused by the carbon including fibrous carbon supported.

[0043] For the fibrous carbon supported on the carrier loaded with transition metal, the average diameter of the fibrous carbon is preferably 20nm to 100nm. If the average diameter of the fibrous carbon is 20nm or more, the agglomeration of the transition metal particles can be further prevented during the reaction, and the conversion rate of the alkane and the selectivity of the olefin corresponding to the alkane can be further improved. On the other hand, if the average diameter of the fibrous carbon is 100nm or less, there is a tendency to further suppress the coating of the transition metal particles by the fibrous carbon, and to easily prevent the catalyst activity from decreasing. Among them, the average diameter of the fibrous carbon is more preferably 25nm or more, and particularly preferably 30nm or more. On the other hand, it is more preferably 95nm or less, and particularly preferably 90nm or less.

[0044] It should be noted that the average diameter of the fibrous carbon in the present invention means: the observation image obtained by using a scanning electron microscope (SEM) is divided into 12 equal grids, and the position with the largest diameter and the position with the smallest diameter of the fibrous carbon are selected from each grid as representative values ​​of the diameter, and the average value of the representative values ​​of the diameter of the fibrous carbon is taken as the average diameter of the fibrous carbon.

[0045] (Method for producing catalyst)

[0046] The method for producing a catalyst according to an embodiment of the present invention comprises the following steps: a step of mixing a solution containing a transition metal compound with a carrier, heating and removing the solvent to obtain a catalyst precursor; and a step of contacting the catalyst precursor with a carbon-containing gas to form a catalyst loaded with transition metal and carbon. By contacting the carbon-containing gas with the catalyst precursor, fibrous carbon can be formed and loaded.

[0047] The step of obtaining the catalyst precursor may include: mixing a solution in which a transition metal compound is dissolved with a carrier, heating to evaporate the solvent to obtain a solid; and pulverizing the solid to obtain a powdered catalyst precursor.

[0048] In the process of obtaining the catalyst precursor, a transition metal compound containing the transition metal of the load can be dissolved in a solvent to prepare a solution, and a carrier is added to the solution to obtain a mixed solution containing the transition metal compound and the carrier. It should be noted that in the present invention, addition is one of mixing, but this means that further mixing can be performed after addition.

[0049] As the carrier used in the step of obtaining the catalyst precursor, at least one selected from the above-mentioned silica, alumina, zirconia, and titania can be used. Among these, alumina is preferred, and γ-alumina is particularly preferred.

[0050] Next, the mixed solution containing the transition metal compound and the carrier can be heated to evaporate the solvent, thereby obtaining a catalyst precursor in which the transition metal is supported on the carrier as a solid. The obtained catalyst precursor (solid) can be pulverized to obtain a powdered catalyst precursor.

[0051] The obtained catalyst precursor can be dried at 20° C. to 200° C. for 1 to 20 hours. The drying temperature is more preferably 60° C. or higher, and further preferably 100° C. or higher, and more preferably 120° C. or lower. The drying time is more preferably 5 hours or more, and more preferably 15 hours or less.

[0052] In addition, the obtained catalyst precursor may be heat treated (calcined) at a high temperature of, for example, 300° C. to 1000° C. for, for example, 2 hours to 30 hours. The temperature of the heat treatment (calcination) is more preferably 400° C. or higher, and more preferably 800° C. or lower. The time of the heat treatment (calcination) is more preferably 3 hours or higher, and more preferably 12 hours or lower.

[0053] The obtained powdered catalyst precursor can be filled into a reactor (e.g., a reaction tube) in a powder state. At this time, the particle size is preferably adjusted in a manner that the pressure loss in the catalyst precursor phase does not become too large. From the viewpoint of suppressing the pressure loss in the catalyst precursor phase and ensuring the surface area of ​​the catalyst precursor, the particle size of the catalyst precursor is preferably as small as possible.

[0054] In addition, from the viewpoint of suppressing the pressure loss in the catalyst precursor phase, the catalyst precursor can be mixed with other materials, or filled after molding. As other materials, fillers (silicon dioxide balls, aluminum oxide balls) that are inactive with respect to the catalyst and do not degrade the catalyst performance can be used. In addition, molding can add a binder that does not degrade the performance of the final catalyst to the catalyst precursor, mix, heat and sinter. As a binder (sintering agent), silica, aluminum oxide, zirconium oxide, and diatomaceous earth can be cited. In addition, as the shape after molding, sheets, particles, spheres, and extrusions can be cited. By molding, strength and operability can be improved.

[0055] Next, the carbon-containing gas is contacted with the obtained catalyst precursor. Thus, it is carbonized by the oxidation reaction of the carbon-containing gas. In addition, at the same time, the transition metal (transition metal oxide) existing in an oxidized state is reduced on the catalyst precursor, and carbon is loaded while the transition metal oxide is reduced, thereby forming a catalyst (alkane dehydrogenation catalyst) loaded with transition metal and carbon. At this time, since the reduction of the transition metal oxide and the loading of carbon can be carried out simultaneously, carbon is generated between the transition metal oxides during the reduction of the transition metal oxide, and the agglomeration of the transition metal crystallites can be suppressed.

[0056] The crystallite diameter of the transition metal supported on the catalyst (carrier) is measured by the ratio of the crystallite diameter of the transition metal after contact with the carbon-containing gas to the crystallite diameter when not in contact with the carbon-containing gas, or the ratio of the crystallite diameter of the transition metal supported on the carrier when the carbon supported on the carrier contains the fibrous carbon to the crystallite diameter of the transition metal supported on the carrier when the carbon supported on the carrier does not contain fibrous carbon, preferably 0.80 or less, more preferably greater than 0.00 and 0.60 or less, and more preferably 0.20 to 0.50. The conditions shown below can be appropriately adjusted in a manner falling within this range.

[0057] In addition, in the determination of the diameter of the transition metal crystallite supported on the carrier, the powder X-ray analysis of the catalyst can be performed, and the peaks belonging to the transition metal crystallites are used to calculate the result by the Scherrer formula. In the present invention, the powder X-ray analysis is determined using SmartLab / R / INP / DX (manufactured by Rigaku). The measurement conditions are carried out using Cu-Kα rays as the X-ray source, a tube voltage of 45kV, and a tube current of 150mA. In addition, for example, when nickel is used as a transition metal, the peak belonging to the (112) plane of 2θ=44° can be used to calculate.

[0058] The basis for the ratio of the crystallite diameter of the transition metal supported on the catalyst (carrier) is as described above, and may be the crystallite diameter of the transition metal when the catalyst precursor is not in contact with the carbon-containing gas, or the crystallite diameter of the transition metal supported on the above-mentioned carrier when the supported carbon does not contain fibrous carbon. The crystallite diameter as such a basis is preferably the crystallite diameter of the transition metal when the catalyst precursor is subjected to hydrogen reduction treatment (contact with a pre-treatment gas that does not contain carbon-containing gas but contains hydrogen). It is particularly preferred to use the crystallite diameter of the transition metal supported on the carrier after the catalyst precursor is subjected to hydrogen reduction treatment (contact with a pre-treatment gas that does not contain carbon-containing gas but contains hydrogen) under the conditions of Comparative Example 3 described later as a basis.

[0059] The carbon-containing gas preferably contains hydrocarbons as a supply source (carbon source) of carbon supported on the catalyst precursor. As the hydrocarbon, an alkane having 2 to 5 carbon atoms is preferred. Examples of the alkane having 2 to 5 carbon atoms include ethane, propane, n-butane, isobutane, n-pentane, and isopentane. These can be used alone or in combination of two or more.

[0060] When the step of preparing the catalyst and the step of preparing the unsaturated hydrocarbon by dehydrogenating alkanes using the obtained catalyst are performed continuously, the carbon source for carbon loading and the alkane raw material for the dehydrogenation reaction may be different hydrocarbons or the same hydrocarbons, but are preferably the same hydrocarbons from the viewpoint of simplification of the process. The carbon source and the alkane raw material in this case are preferably the above-mentioned alkanes having 2 to 5 carbon atoms (e.g., ethane, propane, n-butane, isobutane, n-pentane, isopentane), and isobutane is more preferred.

[0061] The carbon-containing gas may contain an inert gas such as helium and nitrogen in addition to the carbon source.

[0062] The concentration of the carbon source (preferably hydrocarbon) contained in the carbon-containing gas (volume ratio of the carbon source to the carbon-containing gas) is preferably 1% by volume to 30% by volume, and particularly preferably 5% by volume or more, and on the other hand, particularly preferably 20% by volume or less. By making the concentration of the carbon source 1% by volume or more, a sufficient amount of carbon can be loaded more well, and the selectivity of unsaturated hydrocarbons can be further improved. In addition, by making the concentration of the carbon source 30% by volume or less, it is easier to control the loading of excessive carbon, and the decrease in the alkane conversion rate and the selectivity of unsaturated hydrocarbons can be more fully suppressed.

[0063] The temperature in the step of loading carbon on the catalyst precursor (the temperature at which the carbon-containing gas is brought into contact with the catalyst precursor) is preferably 300° C. to 1000° C., and particularly preferably 400° C. or higher, and further preferably 700° C. or lower, and particularly preferably 600° C. or lower. By setting the temperature of the carbon loading step to 300° C. or higher, a more sufficient carbon loading amount can be obtained. In addition, by setting the temperature of the carbon loading step to 1000° C. or lower, a decrease in the carbon loading amount and a decrease in the catalyst activity due to the thermal decomposition reaction of the alkane of the carbon source can be more fully suppressed.

[0064] The pressure in the process of loading carbon on the catalyst precursor (the pressure when the carbon-containing gas is brought into contact with the catalyst precursor) can be appropriately selected according to the type of carbon-containing gas used, and is preferably 0.01MPa to 1MPa. By making the pressure above 0.01MPa, it is possible to easily suppress the detachment of components on the carrier under reduced pressure. In addition, by making the pressure below 1MPa, it is possible to more fully prevent the increase in reactivity caused by pressurization, and it is possible to prevent the excessive loading of carbon on the carrier. Among the above, it is further preferred to be below 0.8MPa, particularly preferably below 0.5MPa, and on the other hand, it is further preferred to be above 0.05MPa. It should be noted that the pressure can be atmospheric pressure (0.101MPa).

[0065] As a method for bringing the carbon-containing gas into contact with the catalyst precursor, a fixed bed flow reaction method can be adopted in which the carbon-containing gas is flowed through a reactor (for example, a reaction tube) filled with the catalyst precursor.

[0066] The W / F when the catalyst precursor is brought into contact with the carbon-containing gas is preferably 0.03 g·min / ml to 0.5 g·min / ml.

[0067] It should be noted that W is the mass (g) of the catalyst precursor filled in the reaction tube, and F is the flow rate (ml / min) of the carbon-containing gas flowing in the reaction tube filled with the catalyst precursor. That is, W / F is the mass of the catalyst precursor filled in the reaction tube relative to the flow rate of the carbon-containing gas flowing in the reactor, and is expressed by the following formula.

[0068] W / F = (the amount of catalyst precursor filled into the reaction tube [g]) / (the flow rate of the carbon-containing gas flowing through the reaction tube [ml / min])

[0069] By making W / F 0.03 g·min / ml or more, it is possible to prevent the carbon loading from becoming insufficient. In addition, by making W / F 0.5 g·min / ml or less, it is possible to prevent the carbon loading from being excessive. Among the above, W / F is particularly preferably 0.05 g·min / ml or more, and on the other hand, it is particularly preferably 0.2 g·min / ml or less.

[0070] (Method for producing unsaturated hydrocarbons from alkanes)

[0071] In the method for producing unsaturated hydrocarbons according to the embodiment of the present invention, the catalyst according to the present invention is brought into contact with a mixed gas containing alkanes and carbon dioxide (hereinafter also appropriately referred to as "reaction gas") to produce unsaturated hydrocarbons from alkanes.

[0072] There are no particular restrictions on the alkane raw material used in the dehydrogenation reaction of alkanes, but alkanes with 2 to 5 carbon atoms are preferred. By making the carbon number 5 or less, the generation of by-products with low carbon atoms due to the decomposition reaction can be suppressed. As alkanes with carbon numbers of 2 to 5, ethane, propane, n-butane, isobutane, n-pentane, and isopentane can be mentioned. They can be used alone or in combination of two or more. Through the dehydrogenation reaction, ethylene is mainly produced from ethane, propylene is mainly produced from propane, butadiene is mainly produced from n-butane, isobutylene is mainly produced from isobutane, pentene is mainly produced from n-pentane, and isoprene is mainly produced from isopentane.

[0073] In the manufacturing method involved in the embodiment of the present invention, the above-mentioned dehydrogenation reaction of alkanes is carried out to manufacture the corresponding unsaturated hydrocarbons. The dehydrogenation reaction is carried out by contacting a mixed gas (reaction gas) containing alkanes and carbon dioxide with the catalyst involved in the present invention. The molar ratio of carbon dioxide to alkanes contained in the mixed gas (reaction gas) is preferably 0.1 to 1.9, more preferably 0.25 or more, and on the other hand, more preferably 1.6 or less. When the molar ratio is less than 0.1, the concentration of carbon dioxide is low, so there is a tendency for reactivity to decrease. On the other hand, when the molar ratio is greater than 1.9, due to the high concentration of carbon dioxide, there is a tendency for selectivity to decrease.

[0074] The mixed gas (reaction gas) may contain, in addition to alkanes and carbon dioxide, inert gases such as helium and nitrogen, water vapor (water), methane, hydrogen, etc., within a range that does not hinder the effects of the present invention.

[0075] The concentration of the alkane in the mixed gas (reaction gas) is preferably 1% by volume to 30% by volume, more preferably 1% by volume or more, further preferably 5% by volume or more, and more preferably 20% by volume or less. By making the concentration of the alkane 1% by volume or more, the decrease in the selectivity of unsaturated hydrocarbons due to the increase in the conversion rate of the alkane can be further suppressed. In addition, by making the concentration of the alkane 30% by volume or less, the decrease in the conversion rate of the alkane can be further suppressed.

[0076] The temperature of the dehydrogenation reaction of the alkane (the temperature at which the mixed gas is brought into contact with the catalyst) is preferably 300° C. to 1000° C., more preferably 400° C. or higher, more preferably 700° C. or lower, and further preferably 600° C. or lower. By setting the temperature of the dehydrogenation reaction to 300° C. or higher, more sufficient catalyst activity can be obtained. In addition, by setting the temperature of the dehydrogenation reaction to 1000° C. or lower, a decrease in the selectivity of unsaturated hydrocarbons and a decrease in catalyst activity due to the thermal decomposition reaction of the alkane can be further suppressed.

[0077] The pressure in the dehydrogenation reaction of alkanes can be appropriately selected according to the type of alkanes used in the reaction, and can usually be set to 1 MPa or less, preferably 0.01 MPa to 1 MPa. The pressure is more preferably 0.8 MPa or less, and further preferably 0.5 MPa or less. On the other hand, it is more preferably 0.05 MPa or more, and further preferably 0.1 MPa or more. It should be noted that the pressure can be atmospheric pressure (0.101 MPa). By making the pressure above 0.01 MPa, the active sites on the catalyst can be more appropriately contacted with alkanes in the reaction, and the selectivity of alkanes can be easily improved. In addition, by making the pressure below 1 MPa, the runaway reaction caused by excessive contact between alkanes in the reaction gas and the generated unsaturated hydrocarbons and the active sites on the catalyst can be further suppressed, and the selectivity of the corresponding olefins can be improved.

[0078] The reaction form adopted in the method for producing unsaturated hydrocarbons according to the embodiment of the present invention is not particularly limited, and the usual form used in the catalytic reaction can be adopted. For example, reaction forms such as fixed bed, moving bed, fluidized bed, etc. can be cited. Among these, from the viewpoint that the device is relatively simple and the process design is also easy, the fixed bed method can be preferably adopted. That is, in the method for producing unsaturated hydrocarbons according to the embodiment of the present invention, the dehydrogenation reaction of alkanes can be carried out by circulating a mixed gas (reaction gas) containing alkanes, carbon dioxide, etc., which are raw materials, in a reactor (such as a reaction tube) filled with the catalyst according to the present invention.

[0079] The W / F in the dehydrogenation reaction of the alkane is preferably 0.001 g·min / ml to 1000 g·min / ml. The W / F is more preferably 0.01 g·min / ml or more, and more preferably 100 g·min / ml or less.

[0080] It should be noted that W is the mass (g) of the catalyst filled in the reaction tube, and F is the flow rate (ml / min) of the mixed gas (reaction gas) containing alkanes and carbon dioxide flowing in the reaction tube filled with the catalyst. That is, W / F is the mass of the catalyst filled in the reaction tube relative to the flow rate of the mixed gas (reaction gas) flowing in the reaction tube, and is expressed by the following formula.

[0081] W / F = (amount of catalyst filled in the reaction tube [g]) / (flow rate of the mixed gas flowing in the reaction tube [ml / min])

[0082] By making the W / F greater than or equal to 0.001 g·min / ml, the reaction time of the alkane with respect to the catalyst can be further ensured, and the conversion rate of the alkane can be improved. In addition, by making the W / F less than or equal to 1000 g·min / ml, the reaction time of the alkane with respect to the catalyst can be further prevented from being excessive, and the generated olefins can be further prevented from reacting on the catalyst to become carbon dioxide, thereby causing a decrease in the selectivity.

[0083] Example

[0084] Hereinafter, the present invention will be described in detail by way of Examples and Comparative Examples, but the present invention is not limited to these Examples.

[0085] (Example 1)

[0086] First, a catalyst (Ni-C / γ-Al2O3 catalyst) was prepared as follows.

[0087] 3.89 parts by mass of nickel nitrate hexahydrate (Wako Pure Chemical Industries, Ltd.) was added to 15 parts by mass of water and dissolved so that the amount of Ni charged to γ-Al 2 O 3 became 20% by mass, thereby obtaining an aqueous solution.

[0088] Then, 4 parts by mass of γ-Al2O3 (Nippon Light Metal Co., Ltd.) was added to the aqueous solution and mixed. Next, the mixture was heated to evaporate water to obtain a solid. The obtained solid was pulverized and vacuum dried at 110°C for 12 hours.

[0089] The pulverized solid was further calcined at 550°C for 1 hour (temperature increase rate 1°C / min). The obtained solid was pulverized again to obtain a powdery catalyst precursor 1 (γ-Al 2 O 3 loaded with nickel).

[0090] The obtained catalyst precursor 1 was placed in a quartz reaction tube with a diameter of 9 mm and a length of 35 mm in a fixed bed flow-type reaction apparatus, and heated to 550° C. while circulating helium. Thereafter, the pretreatment gas containing 85.8% by volume of helium and 14.2% by volume of isobutane was set to various conditions in such a way that W / F became 0.12 g·min / ml. In this way, the pretreatment gas was circulated in the reaction tube for 3 hours to obtain a Ni-C / γ-Al2O3 catalyst in which carbon was supported on the catalyst precursor 1.

[0091] In addition, the obtained catalyst (Ni-C / γ-Al2O3 catalyst) was subjected to powder X-ray analysis. SmartLab / R / INP / DX (Rigaku Corporation) was used for X-ray analysis. The measurement conditions were Cu-Kα rays as the X-ray source, tube voltage 45 kV, and tube current 150 mA. The crystallite diameter of Ni was calculated using the peak attributable to the (112) plane of 2θ=44°.

[0092] Next, using this catalyst, isobutylene was produced from isobutane as follows.

[0093] The catalyst obtained as described above was directly filled in the reaction tube, and reaction gas adjusted to 73.7 volume % helium, 14.2 volume % isobutane, and 12.1 volume % carbon dioxide was flowed in. At this time, each condition was set so that W / F became 0.017 g·min / ml.

[0094] The gas at the outlet of the reaction tube was measured by gas chromatography 6 hours after the start of the flow of the reaction gas, and the isobutane conversion, isobutene selectivity and isobutene yield were determined.

[0095] In addition, "W / F" is represented by the following formula.

[0096] W / F = amount of catalyst precursor or catalyst filled into the reaction tube (g) / supply rate of carbon-containing gas or reaction gas supplied into the reaction tube (ml / min)

[0097] In addition, the isobutane conversion rate, the isobutene selectivity and the isobutene yield are represented by the following formulae.

[0098] Isobutane conversion (%) = (number of moles of isobutane reacted) / (number of moles of isobutane supplied)

[0099] Isobutylene selectivity (%) = (number of moles of isobutylene produced) / (number of moles of isobutane reacted)

[0100] Isobutylene yield (%) = (number of moles of isobutylene produced) / (number of moles of isobutane supplied)

[0101] (Example 2)

[0102] A catalyst (Ni-C / γ-Al2O3 catalyst) was prepared in the same manner as in Example 1 except that the circulation time of the pretreatment gas was changed to 5 hours, and then isobutylene was produced in the same manner as in Example 1.

[0103] In addition, the obtained catalyst (Ni-C / γ-Al2O3 catalyst) was heated to 1000°C using thermogravimetric and differential thermal analysis (TG-DTA), and the amount of carbon carried was measured based on the weight loss at this time. It should be noted that the weight loss when heated to 200°C in the weight change at this time is caused by the detachment of adsorbed water, so the weight loss during the heating process from 200°C to 1000°C is calculated as caused by the carried carbon. Next, a scanning electron microscope (SEM) was used to confirm that the carbon of the catalyst had become fibrous carbon ( Figure 1 and Figure 2 The SEM image is shown in Figure 1. The average diameter of the fibrous carbon was 41.9 nm. The results are shown in Table 1.

[0104] (Example 3)

[0105] A catalyst (Ni-C / γ-Al2O3 catalyst) was prepared in the same manner as in Example 1 except that the flow time of the pretreatment gas was changed to 7 hours, and isobutylene was then produced in the same manner as in Example 1. The results are shown in Table 1.

[0106] (Comparative Example 1)

[0107] A Ni / γ-Al2O3 catalyst was prepared in the same manner as in Example 1 except that the pretreatment gas was not passed, and isobutylene was then produced in the same manner as in Example 1. The results are shown in Table 1.

[0108] (Comparative Example 2)

[0109] The Ni / γ-Al2O3 catalyst was prepared in the same manner as in Example 1, and then isobutylene was produced in the same manner as in Example 1, except that the pretreatment gas was changed to a gas containing 80.0 volume % of helium and 20.0 volume % of hydrogen, and the W / F was changed to 0.0042 g·min / ml and the circulation time of the pretreatment gas was changed to 1 hour. The results are shown in Table 1.

[0110] (Comparative Example 3)

[0111] A Ni / γ-Al 2 O 3 catalyst was prepared in the same manner as in Comparative Example 2 except that the circulation time of the pretreatment gas was changed to 5 hours, and then isobutylene was produced in the same manner as in Example 1.

[0112] The results are shown in Table 1.

[0113] (Comparative Example 4)

[0114] A Ni / γ-Al 2 O 3 catalyst was prepared in the same manner as in Example 1 except that the circulation time of the pretreatment gas was changed to 1 hour, and isobutylene was then produced in the same manner as in Example 1.

[0115] The results are shown in Table 1.

[0116]

Claims

1. A catalyst, characterized in that The transition metal and carbon are supported on a carrier, wherein the carbon comprises fibrous carbon; The amount of the carbon relative to the transition metal is 1000 mass % to 2500 mass %; The catalyst is a catalyst for dehydrogenation of alkanes, The transition metal is nickel.

2. The catalyst according to claim 1, wherein The amount of the carbon relative to the transition metal is 1000 mass % to 2000 mass %.

3. The catalyst according to claim 1 or 2, wherein The carrier is at least one selected from the group consisting of silica, alumina, zirconia and titania.

4. The catalyst according to claim 1 or 2, wherein The carrier is γ-alumina.

5. A method for producing a catalyst, comprising the following steps: A step of mixing a solution containing a transition metal compound with a carrier, heating and removing the solvent to obtain a catalyst precursor, and a step of bringing a carbon-containing gas into contact with the catalyst precursor to form a catalyst loaded with a transition metal and carbon, In the step of forming the catalyst, a carbon-containing gas is brought into contact with the catalyst precursor to form and support fibrous carbon; In the catalyst, the amount of the carbon relative to the transition metal is 1000 mass % to 2500 mass %; The catalyst is a catalyst for dehydrogenation of alkanes, The transition metal is nickel.

6. The method for producing a catalyst according to claim 5, wherein: The step of obtaining the catalyst precursor includes: mixing a solution in which a transition metal compound is dissolved with a carrier, heating to evaporate the solvent to obtain a solid; and pulverizing the solid to obtain a powdery catalyst precursor.

7. The method for producing a catalyst according to claim 5 or 6, wherein: The carbon-containing gas comprises hydrocarbons.

8. The method for producing a catalyst according to claim 7, wherein: The hydrocarbon is an alkane having 2 to 5 carbon atoms.

9. The method for producing a catalyst according to claim 7, wherein: The hydrocarbon is isobutane.

10. The method for producing a catalyst according to claim 7, wherein: The volume ratio of the hydrocarbon to the carbon-containing gas is 1 volume % to 30 volume %.

11. The method for producing a catalyst according to claim 5 or 6, wherein: The temperature of the carbon-containing gas when contacting the catalyst precursor is 300°C to 1000°C.

12. The method for producing a catalyst according to claim 5 or 6, wherein: The ratio W / F of the amount of the catalyst precursor to the supply rate of the carbon-containing gas when the carbon-containing gas contacts the catalyst precursor is 0.03 g·min / mL to 0.5 g·min / mL.

13. The method for producing a catalyst according to claim 5 or 6, wherein: The carrier is at least one selected from the group consisting of silica, alumina, zirconia and titania.

14. The method for producing a catalyst according to claim 5 or 6, wherein: The carrier is γ-alumina.

15. The method for producing a catalyst according to claim 5 or 6, wherein: The crystallite diameter of the transition metal supported on the catalyst is 0.80 or less in terms of the ratio of the crystallite diameter of the transition metal after contact with the carbon-containing gas to the crystallite diameter when not contacted with the carbon-containing gas.

16. A method for producing unsaturated hydrocarbons, comprising contacting the catalyst according to claim 1 with a mixed gas containing an alkane and carbon dioxide to produce unsaturated hydrocarbons from the alkane.

17. The method for producing unsaturated hydrocarbons according to claim 16, wherein In the mixed gas, the molar ratio of the carbon dioxide to the alkane is 0.1 to 1.

9.

18. The method for producing unsaturated hydrocarbons according to claim 16 or 17, wherein The alkane is an alkane having 2 to 5 carbon atoms.

19. The method for producing unsaturated hydrocarbons according to claim 16 or 17, wherein: The alkane is isobutane.

20. The method for producing an unsaturated hydrocarbon according to claim 16 or 17, wherein: The temperature of the mixed gas when contacting the catalyst is 300°C to 1000°C.

21. The method for producing unsaturated hydrocarbons according to claim 16 or 17, wherein: The ratio W / F of the amount of the catalyst when the mixed gas contacts the catalyst to the supply rate of the mixed gas is 0.001 g·min / mL to 1000 g·min / mL.

22. A method for producing unsaturated hydrocarbons, comprising producing a catalyst by the method according to claim 5, and then bringing a mixed gas containing an alkane and carbon dioxide into contact with the obtained catalyst to produce unsaturated hydrocarbons from the alkane.

23. The method for producing unsaturated hydrocarbons according to claim 22, wherein: In the mixed gas, the molar ratio of the carbon dioxide to the alkane is 0.1 to 1.9.

Citation Information

Patent Citations

  • Dehydrogenation catalyst

    JP1997075732A

  • Method for producing unsaturated hydrocarbon and dehydrogenation catalyst used for the method

    JP2013163647A

  • Method for producing oxidative dehydrogenation catalyst and alkene

    JP2014140827A

  • Catalyst and hydrocarbon conversion process using said catalyst

    JP2018520858A

  • Catalyst and process

    CN102459135A